Fillable and unfillable gaps in plant transcriptome under field and controlled environments - Hashida, Yoichi; Tezuka, Ayumi; Nomura, Yasuyuki; Kamitani, Mari; Kashima, Makoto; Kurita, Yuko; Nagano, Atsushi J. (Plant, cell and environment, 2022)
The differences between plants grown in field and in controlled environments have long been recognized. However, few studies have addressed the underlying molecular mechanisms. To evaluate plant responses to fluctuating environments using laboratory equipment, we developed SmartGC, a high‐performance growth chamber that reproduces the fluctuating irradiance, temperature and humidity of field environments. We analysed massive transcriptome data of rice plants grown under field and SmartGC conditions to clarify the differences in plant responses to field and controlled environments. Rice transcriptome dynamics in SmartGC mimicked those in the field, particularly during the morning and evening but those in conventional growth chamber conditions did not. Further analysis revealed that fluctuation of irradiance affects transcriptome dynamics in the morning and evening, while fluctuation of temperature affects transcriptome dynamics only in the morning. We found upregulation of genes related to biotic and abiotic stress, and their expression was affected by environmental factors that cannot be mimicked by SmartGC. Our results reveal fillable and unfillable gaps in the transcriptomes of rice grown in field and controlled environments and can accelerate the understanding of plant responses to field environments for both basic biology and agricultural applications. Summary Statement Diurnal transcriptome dynamics of rice grown in fluctuating field and controlled environments are different mainly in the morning and evening, which are affected by light and temperature in the morning, while only by light in the evening. We also found field‐specific gene expression.